Three decades of household food availability according to NOVA - Brazil, 1987-2018 - Levy, Renata Bertazzi; Andrade, Giovanna Calixto; Cruz, Gabriela Lopes da; Rauber, Fernanda; Louzada, Maria Laura da Costa; Claro, Rafael Moreira; Monteiro, Carlos Augusto (Revista de saúde pública, 2022)
To evaluate the trend of household food acquisition according to the NOVA classification in Brazil between 1987-1988 and 2017-2018. We used household food acquisition data from five editions of the Pesquisas de Orçamentos Familiares (Household Budget Surveys), conducted by the Instituto Brasileiro de Geografia e Estatística (Brazilian Institute of Geography and Statistics), in the years 1987-1988, 1995-1996, 2002-2003, 2008-2009, and 2017-2018. All reported foods were categorized according to the NOVA classification. The household availability of food groups and subgroups was expressed through their share (%) in total calories, for all Brazilian families, by household situation (urban or rural), for each of the five geographic regions of the country, by fifths of the household income per capita distribution (2002-2003, 2008-2009 and 2017-2018 surveys), and for the 11 main urban regions of the country (1987-1988, 1995-1996, 2002-2003, 2008-2009 and 2017-2018 surveys). Linear regression models were used to assess the trend of increasing or decreasing food purchases. The diet of the Brazilian population is still composed predominantly of foods in natura or minimally processed and processed culinary ingredients. However, our findings point to trends of increasing share of ultra-processed foods in the diet. This increase of 0.4 percentage points per year between 2002 and 2009 slowed down to 0.2 percentage points between 2008 and 2018. The consumption of ultra-processed food was higher among households with higher income, in the South and Southeast regions, in urban areas, and in metropolitan regions. Our results indicate an increase in the share of ultra-processed foods in the diet of Brazilians. This is a worrisome scenario, since the consumption of such foods is associated with the development of diseases and the loss of nutritional quality of the diet.